Modular design of a hybrid hydrogel for protease-triggered enhancement of drug delivery to regulate TNF-α production by pro-inflammatory macrophages - Nguyen, Dang Tri (2022)
Systemic drug administration has conventionally been prescribed to alleviate persistent local inflammation which is prevalent in chronic diseases. However, this approach is associated with drug-induced toxicity, particularly when the dosage exceeds that necessitated by pathological conditions of diseased tissues. Herein, we developed a modular hybrid hydrogel which could be triggered to release an anti-inflammatory drug upon exposure to elevated protease activity associated with inflammatory diseases. Modular design of the hybrid hydrogel enabled independent optimization of its protease-cleavable and drug-loaded subdomains to facilitate hydrogel formation, cleavability by matrix-metalloprotease-9 (MMP-9), and tuning drug release rate. In vitro study demonstrated the protease-triggered enhancement of drug release from the hybrid hydrogel system for effective inhibition of TNF-α production by pro-inflammatory macrophages and suggested its potential to mitigate drug-induced cytotoxicity. Using non-invasive imaging to monitor the activity of reactive oxygen species in biomaterial-induced host response, we confirmed that the hybrid hydrogel and its constituent materials did not induce adverse immune response after 5 days following their subcutaneous injection in immuno-competent mice. We subsequently incorporated this hybrid hydrogel onto a commercial wound dressing which could release the drug upon exposure to MMP-9. Together, our findings suggested that this hybrid hydrogel might be a versatile platform for on-demand drug delivery via either injectable or topical application to modulate inflammation in chronic diseases.